PEMBELAJARAN TEMATIK UNTUK MENYEIMBANGKAN KERJA OTAK KANAN DAN OTAK KIRI - ErlinLadyawati ErlinLadyawati; Prayogo Prayogo (WAHANA, 2013)
Thematic study is an activity of an intregrated learning. Activity by intregrating various kinds of a learning materials in one theme so that it can give valueble experience to the students. The activities in this thesis describes the way of right brain and left brain work. This theses is done in the third classes of Elementary School with the "Kesehatan (Health)" theme. The subthemes which are developed are "Cleanline", "Healthy life", "Healthy food", and "Healthy Body". The target that will be reached through this theses is to describe the right and brain work at the time of thematic learning process. The population of this theses is the third class students of Goverment Elementary School Kalisari II Surabaya, while the samples are ony the student of 3B class. This study (research) is descriptive qualitative research. The model of developing lesson plan use the model that is developed by kemp which has nine components : deciding the theme, students characteristics analyse, learning goals, deciding the materials, deciding the pre activities of learning (pre activities), teaching activities, aditional tools, evaluationn, and revision. The techuqe of collecting data in this theses is none test and lest. None test is used to classyfy (to group) the students into, two groups these are the groups of student who are night brain dominant and the group of student who are dominant on the left brain by using questionairs, and to ralidate the learning validation tools, tools on the other hand test technique is use to know the result of the study. The result of learning test is used to know the mastery work on the right and left brai. From the result of thestudy it is know that 86% ofthe number of the student learning are all done. So it can be concluded that thematic learning can balance the work of right brains and left brains.